Perancangan Ruang Pendingin Karkas Ayam Broiler Memanfaatkan Sumber Energi Hibrida - Hafiz, Rahmat; Haris, Haris; Effiandi, Nota; Chadry, Rivanol; Saputra, Feri (Jurnal Teknik Mesin, 2024)
Small-scale broiler farming in Indonesia often suffers losses due to high production costs. In addition to rising feed prices, these losses are frequently caused by chickens that are ready for harvest being unsold in the market due to a decline in purchasing power. One solution that farmers can implement is to slaughter the chickens at the appropriate harvest time and store the carcasses in cooling rooms to sell them when market prices increase. This study aims to design and specify cooling storage equipment to store broiler carcasses using a combination of commercial and solar energy sources. The research begins by determining the cooling load of the system, specifying refrigeration components, evaluating solar energy potential at the location, and designing the required electrical system. Solar energy potential was calculated based on meteorological data obtained from an online database and processed using the PvSyst 7.2 application. Based on the analysis, the cooling storage requires 4.69 kW of power to reach optimal temperature within 6 hours, with a COPR value of 2.2. Meanwhile, the solar energy potential at the installation site is 4.44 kWh/m²/day, enabling the solar power system (PLTS) to generate an estimated annual energy output of 1802 kWh with a Performance Ratio (PR) of 65.07% and a Solar Fraction (SF) of 91.85%.